To solve the given problems, we need to perform function composition. This involves substituting one function into another. For each part:
(a) For \((f \circ g)(x)\), substitute \(g(x)\) into \(f(x)\).
(b) For \((g \circ f)(x)\), substitute \(f(x)\) into \(g(x)\).
(c) For \((f \circ f)(x)\), substitute \(f(x)\) into itself.
For the specific values:
(e) Evaluate \((f \circ g)(x)\) at \(x = -3\).
(f) Evaluate \((g \circ f)(x)\) at \(x = -6\).
We are given two functions:
- \( f(x) = x^2 - 7x \)
- \( g(x) = x - 9 \)
To find the compositions, we substitute one function into another.
Substitute \( g(x) \) into \( f(x) \):
\[
f(g(x)) = f(x - 9) = (x - 9)^2 - 7(x - 9)
\]
Simplify:
\[
= (x^2 - 18x + 81) - (7x - 63) = x^2 - 25x + 144
\]
Substitute \( f(x) \) into \( g(x) \):
\[
g(f(x)) = g(x^2 - 7x) = (x^2 - 7x) - 9 = x^2 - 7x - 9
\]
Substitute \( f(x) \) into itself:
\[
f(f(x)) = f(x^2 - 7x) = (x^2 - 7x)^2 - 7(x^2 - 7x)
\]
Simplify:
\[
= (x^4 - 14x^3 + 49x^2) - (7x^2 - 49x) = x^4 - 14x^3 + 42x^2 + 49x
\]
Evaluate the compositions at specific values.
Substitute \(-3\) into \((f \circ g)(x)\):
\[
f(g(-3)) = f(-3 - 9) = f(-12) = (-12)^2 - 7(-12) = 144 + 84 = 228
\]
Substitute \(-6\) into \((g \circ f)(x)\):
\[
g(f(-6)) = g((-6)^2 - 7(-6)) = g(36 + 42) = g(78) = 78 - 9 = 69
\]
- (a) \((f \circ g)(x) = x^2 - 25x + 144\)
- (b) \((g \circ f)(x) = x^2 - 7x - 9\)
- (c) \((f \circ f)(x) = x^4 - 14x^3 + 42x^2 + 49x\)
- (e) \((f \circ g)(-3) = \boxed{228}\)
- (f) \((g \circ f)(-6) = \boxed{69}\)